2021
DOI: 10.1590/1982-0224-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanization and environmental heterogeneity on fish assemblages in small streams

Abstract: The structure of freshwater assemblages may be driven directly by urbanization or indirectly by a reduction in environmental heterogeneity (EH). Disentangling the effects of urbanization and EH requires uncorrelated proxies of each of these factors. We assessed the effects of the degree of urbanization and EH on the structure of fish assemblages. We sampled fish in 45 streams located in the urban area of Cuiabá. We assessed the effects of urbanization and EH on rarefied fish species richness (Srarefied), the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Furthermore, the lower basin is also an urban-, and industry-intensive area (Figures 1 and 2) [56]. Urbanization and industrialization generally lead to habitat degradation through ways involving hydrological instability induced by high impervious surface coverage and runoff conveyance, pollutant inputs, stream channelization, water temperature fluctuations induced by riparian vegetation degradation, and untreated sewage inputs [42,54,57]. Since ecological conditions were systematically degraded in the downstream catchment, sensitive species gradually disappeared from local communities, resulting in the reduction of local biotic heterogeneity [42,58,59].…”
Section: Shifts In Longitudinal Fish Assemblage Patternsmentioning
confidence: 99%
“…Furthermore, the lower basin is also an urban-, and industry-intensive area (Figures 1 and 2) [56]. Urbanization and industrialization generally lead to habitat degradation through ways involving hydrological instability induced by high impervious surface coverage and runoff conveyance, pollutant inputs, stream channelization, water temperature fluctuations induced by riparian vegetation degradation, and untreated sewage inputs [42,54,57]. Since ecological conditions were systematically degraded in the downstream catchment, sensitive species gradually disappeared from local communities, resulting in the reduction of local biotic heterogeneity [42,58,59].…”
Section: Shifts In Longitudinal Fish Assemblage Patternsmentioning
confidence: 99%
“…While land use variables provide the first evidence that urbanization and agriculture change fish communities, pinpointing the specific variables associated with these land uses can give additional insight into what environmental monitors should be measured when completing bioassessments (Waite et al, 2021;Iacarella, 2022). For example, Stoczynski et al (2021) found that dam density affected how species replaced one another across the landscape, Ortega et al (2021) identified impervious surfaces as a proxy for urbanization, and Waite et al (2021) highlighted how contaminants in water and sediment were just one of multiple urbanization and agricultural stressors. Thus, disentangling anthropogenic effects from 'natural' environmental variables in metacommunity analyses may increase our ability to explain factors structuring beta diversity within metacommunities (Duarte et al, 2018;Gianuca et al, 2018).…”
Section: Introductionmentioning
confidence: 99%